Teacher Education In India Viewed Through The Lens of National Education Policy – 2020 - Kaushi, Pallavi; Ahmad, Jasim; Khan, Aerum (Voices of Teachers and Teacher Educators, 2021)
The current National Educational Policy was announced, passed by the Union Cabinet and implemented in 2020 after almost a year long debate on its draft, which was made public in 2019. The policy is revolutionary in outlook as it claims to bring great changes and breaks the stagnation by transforming school education system from 10+2 to 5+3+3+4 with the addition of three years of Early Childhood Care and Education (ECCE), integrated teacher education programmes, establishment of PARAKH, NTA, Higher Education Commission and many more new initiatives. School education is the foundation of the robust education system of the country and teacher education is the heart and soul, which prepare and pump teachers into the school education system. This paper reflects the perspectives of in-service teacher educators teaching in various teacher education colleges in Delhi with regard to the provisions and reinvention of teacher education as envisaged by the NEP 2020. A total of 30 teacher educators teaching in Delhi-based teacher education institutions were approached purposively. An open-ended questionnaire was administered using google form followed by an online interview with all the respondents to have cross questions and seeking clarity on their responses to the questionnaire. This paper presents the details of the study and its findings, which is encouraging but challenging and full of apprehensions as well.